Peningkatan Kemampuan Memahami Perubahan Wujud Melalui Video Interaktif Berbasis CTL pada Siswa Slow Learner : Improving the Ability to Understand Changes in State of Matter Among Slow Learners Using CTL-Based Interactive Videos - Neli Mailawati; Rendy Roos Handoyo (ITScience (Information Technology and Science), 2026)
This study was motivated by the low ability of second-grade elementary school students—specifically those at risk of being